Description Of Perceptions Of The Donning And Doffing Of Personal Protective Equipment In Unpad Nursing Students Class Of 2017 - Rizkika Nur Amalia; Etika Emaliyawati; Ati Surya Mediawati (Universitas Padjadjaran, 2021)
Personal protective equipment (PPE) is one of the standard precautions to reduce the risk of infection spreading. Nursing students are expected to have the proper knowledge and attitude regarding the donning and doffing of PPE as taught during the educational period. This study was intended to understand the knowledge and attitude regarding the donning and doffing of PPE on the students in the Faculty of Nursing Universitas Padjadjaran class of 2017 who will attend nurse profession education.The method of this study was descriptive quantitative. The population of this study was the students in the Faculty of Nursing Universitas Padjadjaran class of 2017. The sampling method was total sampling with a response rate of 82.7% (n=205). The instrument used was an online questionnaire of knowledge and attitude regarding PPE built by the researcher. The validity assessed were the construct validity and the content validity. The reliability had Cronbach's alpha value of 0.913 (knowledge) and 0.808 (attitude). The data analysis used median and frequency distribution.The study result showed that 113 respondents (55.1%) had proper knowledge regarding PPE while 92 respondents (44.9%) lacked knowledge regarding PPE. The variable study result showed that 111 respondents (54.1%) had a positive attitude toward PPE and 94 respondents (45.9%) had a negative attitude toward PPE.More than half the students in the Faculty of Nursing Universitas Padjadjaran class of 2017 had proper knowledge and a positive attitude. Knowledge and attitude can be affected by training, experience, and the availability of PPE. Practice and training concerning PPE during the educational period can increase the ability of the students to donning and doffing PPE properly because the students can easily understand the basic principles and standard practices and implement them consistently. Therefore, to increase the knowledge and attitude, the revitalization of education and training is required.